Persistent Encopresis, Enuresis, and Anxiety in a 7-Year-Old Girl. Issue 8 (October 2017) - Nelson, Theodora; Chae, Heekyung; Anbar, Ran D.; Stein, Martin T.
Abstract : CASE: Sonia is a 7-year-old old girl who was referred to the Developmental-Behavioral Pediatrics Clinic by the Pediatric Urology Clinic because of persistent wetting and soiling behaviors. Since age 3 years, she has had a history of encopresis (and wetting) for which she has seen gastroenterology and urology specialists. The mother reports that Sonia has accidents almost daily, and she is not upset when sitting in her urine or feces. She dislikes going into the bathroom or sitting on the toilet by herself. She participated in a behavior modification program associated with the pediatric urology clinic, which helps children learn healthy voiding habits and achieve continence. Sonia also has anxious behaviors. She bites her nails and chews on her hair or shirt. She is afraid of small spaces such as those between the bed and the wall and needs to have stuffed animals cover them. Other instances that trigger her anxious behaviors include loud noises, having a substitute teacher, being separated from her mother, and going to certain bathrooms or new places. She also has severe tantrums, which involve throwing and breaking objects, kicking, and hitting her head against doors. A cognitive behavioral therapy program was recommended to target anxiety symptoms, in addition to timed toileting after meals and polyethylene glycol. At a clinic visit several months later, symptoms of anxiety, encopresis, and enuresis persisted. Cognitive behavior therapy was continued and sertraline 25 mg was prescribed for anxiety. In addition, she was referred to a pediatrician who specializes in relaxation techniques and hypnotherapy. Sonia showed modest improvement with these interventions. There were fewer episodes of angry outbursts and a decrease in soiling and wetting, but at times, but she continued to have intermittent periods of wetting and soiling and fear of going to the bathroom by herself persisted. (This Challenging Case extends observations reviewed in a previous Challenging Case: J Dev Behav Pediatr 2010;531:513–515; DOI: 10.1097/DBP.0b013e3181e5a464.)